2000
DOI: 10.1121/1.1336896
|View full text |Cite
|
Sign up to set email alerts
|

Empirical relationships between acoustic parameters in human soft tissues

Abstract: Previously published summaries of sound speed, density, attenuation coefficient, and nonlinearity parameter, B/A, in human soft tissues are quantitatively analyzed. A highly significant empirical linear relationship is found to hold between sound speed and density for a wide range of soft tissues, including adipose, parenchymal, muscular, and connective tissues as well as body fluids. Even higher correlations occur between nondimensional parameters describing density variations and compressibility variations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
223
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(235 citation statements)
references
References 25 publications
8
223
0
4
Order By: Relevance
“…The maximum temperature elevation is approximately 7.5˚C, which means that one could afford to slightly defocus the US beam to increase the insonified volume. Furthermore, [39] showed that the mean absorption coefficient of human soft tissues is approximately 0.54 dB/cm (or 6.2 Np/m) at 1 MHz, higher than that of glycerol (3.6 Np/(m•MHz)). This means that even if an in vivo evaluation will introduce thermal dissipation due to blood perfusion, we could still expect good performance on small animals, depending on the insonified tissue.…”
Section: Mild Hyperthemiamentioning
confidence: 99%
“…The maximum temperature elevation is approximately 7.5˚C, which means that one could afford to slightly defocus the US beam to increase the insonified volume. Furthermore, [39] showed that the mean absorption coefficient of human soft tissues is approximately 0.54 dB/cm (or 6.2 Np/m) at 1 MHz, higher than that of glycerol (3.6 Np/(m•MHz)). This means that even if an in vivo evaluation will introduce thermal dissipation due to blood perfusion, we could still expect good performance on small animals, depending on the insonified tissue.…”
Section: Mild Hyperthemiamentioning
confidence: 99%
“…This works by simulating the propagation of ultrasound waves through a map of the individual patient's Figure 1: Relationship between the density of the skull bone, derived from CT, and the compressional sound speed. Values taken from Connor et al [19], Mast et al [20], Aubry et al [5], and Pichardo et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…5 shows the change in the density and acoustic impedance according to the olive-oil composition ratio. Table 2 compares the acoustic properties of the fabricated fat phantom in this study, subcutaneous fat tissue [12][13][14], and fat tissue of the breast area [10] as typical fat tissue. From a comparison of the subcutaneous fat tissue and the fat tissue of the breast area, the sound velocity of the subcutaneous fat tissue was 40 m/s higher than the fat tissue of the breast area.…”
Section: Resultsmentioning
confidence: 99%